Pengaruh Karakteristik Pekerjaan, Karakteristik Individu Dan Keterlibatan Karyawan Terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan Kantor Camat Malinau Utara, Kalimantan Utara) - Tami Erliani; Budi Wahono; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the influence of job characteristics variables, individual characteristics and employee involvement on employee performance. This research uses a case study at the Malinau Utara District Office, North Kalimantan, which was selected by accidental sampling.Determining the number of samples using saturated or census sampling techniques and obtained the results of 44 respondents. Data collection was carried out using a questionnaire. Data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Partial test (t test), Simultaneous test (F test ) and Determination Coefficient Test (Adjusted R2 ) and the process of analysis using SPSS 21. The results of the study stated that the variables of job characteristics and individual characteristics have an effect on employee performance while employee involvement has no effect. Keywords : Job Characteristics, Individual Characteristics, Employee Engagement, Employee Performance